Perfusion Functional MRI Reveals Cerebral Blood Flow Pattern under Psychological Stress - Jiongjiong Wang; Hengyi Rao; Gabriel S. Wetmore; Patricia M. Furlan; Marc Korczykowski; Dinges, David F.; Detre, John A. (Proceedings of the National Academy of Sciences - PNAS, 2005)
Despite the prevalence of stress in everyday life and its impact on happiness, health, and cognition, little is known about the neural substrate of the experience of everyday stress in humans. We use a quantitative and noninvasive neuroimaging technique, arterial spin-labeling perfusion MRI, to measure cerebral blood flow (CBF) changes associated with mild to moderate stress induced by a mental arithmetic task with performance monitoring. Elicitation of stress was verified by self-report of stress and emotional state and measures of heart rate and salivary-cortisol level. The change in CBF induced by the stress task was positively correlated with subjective stress rating in the ventral right pref rontal cortex (RPFC) and left insula/putamen area. The ventral RPFC along with right insula/putamen and anterior cingulate showed sustained activation after task completion in subjects reporting a high stress level during arithmetic tasks. Additionally, variations of baseline CBF in the ventral RPFC and right orbitofrontal cortex were found to correlate with changes in salivary-cortisol level and heart rate caused by undergoing stress tasks. We further demonstrated that the observed right prefrontal activation could not be attributed to increased cognitive demand accompanying stress tasks and extended beyond neural pathways associated with negative emotions. Our results provide neuroimaging evidence that psychological stress induces negative emotion and vigilance and that the ventral RPFC plays a key role in the central stress response.